Integration mesoporous surface and hollow cavity into PtPdRh nano-octahedra for enhanced oxygen reduction electrocatalysis. (10th October 2019) - Deng, Kai; Xu, You; Li, Yinghao; Dai, Zechuan; Wang, Ziqiang; Li, Xiaonian; Wang, Hongjing; Wang, Liang
Abstract: Design and synthesis of Pt-based nanocrystals with controlled structural diversity and complexity can potentially bring about multifunctional properties. In this work, we present a facile two-step strategy for the construction of the PtPdRh mesoporous octahedral nanocages (PtPdRh MONCs). This unique nanoarchitectonics rationally integrates multiple advantages (i.e. the octahedral shape, hollow cavity and mesoporous surface) into one catalyst, which facilitates the efficient utilization of noble metal atoms at both of the interior and exterior surfaces. As expected, the resultant PtPdRh MONCs could effectively catalyze the oxygen reduction reaction (ORR) under acidic conditions. The demonstrated ORR activity and catalytic durability are superior to the commercial Pt/C catalyst. The present study would provide a general guidance for architectural and compositional engineering of noble metal nanocrystals with desired functionalities and properties.